EFFECTIVENESS OF HOT ISOSTATIC PRESSING ON HEALING OXIDE FILM DEFECTS IN CAST ALUMINIUM ALLOYS - Nyahumwa, C. (Tanzania Journal of Engineering and Technology, 2018)
EFFECTIVENESS OF HOT ISOSTATIC PRESSING ON HEALING OXIDE FILM DEFECTS IN CAST ALUMINIUM ALLOYS